Erosion of Trust in the Medical Profession in India: Time for Doctors to Act - Sumit Kane; Michael Calnan (Kerman University of Medical Sciences, 2017)
In India, over the last decade, a series of stewardship failures in the health system, particularly in the medical profession, have led to a massive erosion of trust in these institutions. In many low- and middle-income countries (LMICs), the situation is similar and has reached crisis proportions; this crisis requires urgent attention. This paper draws on the insights from the recent developments in India, to argue that a purely control-based regulatory response to this crisis in the medical profession, as is being currently envisaged by the Parliament and the Supreme Court of India, runs the risk of undermining the trusting interpersonal relations between doctors and their patients. A more balanced approach which takes into account the differences between system and interpersonal forms of trust and distrust is warranted. Such an approach should on one hand strongly regulate the institutions mandated with the stewardship and qualities of care functions, and simultaneously on the other hand, initiate measures to nurture the trusting interpersonal relations between doctors and patients. The paper concludes by calling for doctors, and those mandated with the stewardship of the profession, to individually and collectively, critically self-reflect upon the state of their profession, its priorities and its future direction.